Local crop development: An annotated bibliography - Heide, W.M. van der; Tripp, R.; Boef, W.S. de; International Plant Genetic Resources Institute (1996)
Published in collaboration with CGN, CPRO-DLO, ODI and IPGRI. The interest in in situ and community conservation approaches has caused significant confusion among professional conservationists. A change in the conservation perspective has suddenly placed genebanks in a complementary role next to indigenous and local conservation efforts. Conservation is now linked to direct utilization efforts by communities in local crop development. Further confusion has arisen through the increased number of professionals involved in debates on conservation. Development elements have been integrated into the conservation paradigm. Utilization perspective and local knowledge have widened the spectrum of conservation. This range of interests and viewpoints has led to many different interpretations of what conservation and local crop development are all about. The intention of this bibliography is to bring some clarity to the literature available on the changing perspective on the conservation of biodiversity, farmer's management of genetic diversity and local crop development activities.